Pengembangan Instrumen Tes Kemampuan Pemecahan Masalah Mahasiswa pada Topik Usaha dan Energi - Muhammad Reyza Arief Taqwa; Endang Purwaningsih; Sulur Sulur (Jurnal Penelitian Pembelajaran Fisika, 2020)
This article aims to describe the results of the development of a test instrument for problem solving abilities. Topics focused on Work and Energy. This article was the result of research and development (R&D) by adapting the 4D model. Define done by analyzing the needs that exist in Universitas Negeri Malang. The design phase was carried out by determining the question indicators that were in accordance with the CPMK course in Basic Physics I, the appropriate cognitive domain, determining the answer key, and scoring rubric. The develop phase was carried out in three steps, namely validation by experts, legibility testing, and empirical testing. The results of research and development obtained intrument tests of feasible problem solving abilities based on the results of (1) the validators state that the instruments in the category were very feasible; (2) the readability test respondents state that the instrument is very good; and (3) empirical tests related to validity and reliability with the results of all items are valid at a significance level of 0.05 and reliable with Cronbach's Alpha coefficient is 0.746.